Surgical revascularization of myocardium in population of young women. Is it a group of increased operative risk? - Dziuba, Michal; Jander, Slawomir; Zwolinski, Radoslaw; Chizynski, Krzysztof (Archives of Medical Science, 2009)
Occurrence of myocardial infarction and advanced atheromatosis of coronary arteries in premenopausal women is unusual. Surgical revascularization of myocardium as an established method of ischaemic heart disease (IHD) management is more often used in this subset of patients. In recent years there have been some studies indicating better outcome of female patients after cardiac surgery, especially in the long term, but it is generally believed that women are more exposed to complications and have poorer prognosis after myocardial revascularization procedures compared with males, especially in the youngest groups. It seems that physiological protectors of the cardiovascular system which are present in a healthy population of young women are not effective in a subset with IHD undergoing coronary artery bypass grafting (CABG). Young women with IHD may represent a high-risk group with a hospital mortality higher than men after CABG surgery.